2D Hybrid perovskite incorporating cage-confined secondary ammonium cations toward effective photodetection. Issue 4 (15th December 2021) - Hua, Lina; Chen, Huaixi; Han, Shiguo; Xu, Haojie; Lu, Lei; Tang, Liwei; Wang, Beibei; Luo, Junhua; Sun, Zhihua
Abstract : A Ruddlesden–Popper hybrid perovskite was assembled by confining secondary ammonium cations into the inorganic framework, for which 2D quantum-well motifs render a fascinating photoresponse and effective photodetection properties. Abstract : By confining the secondary dimethylammonium (DMA) cation in a distorted perovskite cavity, we assembled a new 2D Ruddlesden–Popper metal halide perovskite of (i-BA)2 (DMA)Pb2 Br7 (i-BA = n -isobutylammonium), in which the DMA cation templates its inorganic perovskite framework and the quantum-well motif renders a fascinating photoresponse. Crystal-based planar arrays exhibit effective photodetection behaviors, including a notable detectivity (∼5.6 × 10 12 Jones), a high responsivity (∼1.25 A W −1 ) and a large switching ratio (∼1.5 × 10 3 ). These properties result from its low dark current restricted to the hopping barrier of the insulated organic bilayer and a strong in-plane photoresponse correlated with the perovskite network. This work throws light on the targeted exploration of photosensitive candidates in the family of organic–inorganic hybrid perovskites, as well as high-performance devices.